Case reportLeft atrial myxoma crossing the mitral valve - Faizi, Fakhraddin; Dadjou, Yahya; Bigdeli, Hamid; Hejazi, Fakhraddin (Archives of Medical Science, 2005)
In this article, we report a 79-year-old man with a large mobile and pediculated mass in left atrium crossing the mitral valve in diastol and enter the left ventricle. Transthorasic two-dimensional echocardiography showed the big neoplastic mass attached to interatrial septum (IAS) and measured 7x4.5 cm. The patient presented signs and symptoms of Transient Ischemic Attack (TIA) with aphasia, dysphagy suddenly developed 24 hours earlier to admission. Brain axial CT scan showed a hypodense area in the left parietal lobe and a hypodense trigonal shaped area in the left temporal lobe. The surgical approach used for resection of this tumour was an isolated left atriotomy that provided excellent exposure and safe excision.